PENGEMBANGAN MODUL AJAR MATA KULIAH KONSEP DASAR SAINS BERBANTUAN ETNOID (ETNOSCIENCE ANDROID) UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS MAHASISWA PGSD - Faudina Permatasari; Vindhy Dian Indah Pratika; Evi Fitriana (STAI Nurul Falah Airmolek, 2025)
The results of the initial analysis showed that 68% of students had difficulty in identifying the application of vibration and wave concepts, even though this understanding is very important in elementary school level learning. This study aims to analyze the feasibility of teaching materials and the ability to understand the concepts of undergraduate PGSD students at Bhinneka PGRI University related to vibration and wave material designed with a scientific approach using Etnoid assistance. This research uses the 4D method developed by Thiagarajan, which consists of four main stages: (1) Defining, (2) Designing, (3) Development, and (4) Deployment. The research subjects included students of the Bhinneka PGRI University Elementary School Teacher Education Study Program, with instruments in the form of validation questionnaires by material and media experts, as well as student perception questionnaires of the modules produced. The results showed that the Etnoid-based learning module has a validity level of 92.95% which is included in the very valid category, practicality of 95% with a very practical category, and effectiveness of 0.87 which is included in the very effective category. Based on the results of the analysis, the developed Etnoid-based module was declared very feasible to use and able to improve students' science process skills.